Optimizing CSP1 analogs for modulating quorum sensing in Streptococcus pneumoniae with bulky, hydrophobic nonproteogenic amino acid substitutions. Issue 3 (3rd February 2022) - Milly, Tahmina A.; Buttner, Alec R.; Rieth, Naomi; Hutnick, Elizabeth; Engler, Emilee R.; Campanella, Alexandra R.; Lella, Muralikrishna; Bertucci, Michael A.; Tal-Gan, Yftah
Abstract : The prompt appearance of multiantibiotic-resistant bacteria necessitates finding alternative treatments that can attenuate bacterial infections while minimizing the rate of antibiotic resistance development. Abstract : The prompt appearance of multiantibiotic-resistant bacteria necessitates finding alternative treatments that can attenuate bacterial infections while minimizing the rate of antibiotic resistance development. Streptococcus pneumoniae, a notorious human pathogen, is responsible for severe antibiotic-resistant infections. Its pathogenicity is influenced by a cell-density communication system, termed quorum sensing (QS). As a result, controlling QS through the development of peptide-based QS modulators may serve to attenuate pneumococcal infections. Herein, we set out to evaluate the impact of the introduction of bulkier, nonproteogenic side-chain residues on the hydrophobic binding face of CSP1 to optimize receptor-binding interactions in both of the S. pneumoniae specificity groups. Our results indicate that these substitutions optimize the peptide–protein binding interactions, yielding several pneumococcal QS modulators with high potency. Moreover, pharmacological evaluation of lead analogs revealed that the incorporation of nonproteogenic amino acids increased the peptides' half-life towards enzymatic degradation while remaining nontoxic. Overall, our data convey key considerations for SAR using nonproteogenic amino acids, which provide analogs with better pharmacological properties.